2011
DOI: 10.1186/1742-2094-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced spiral ganglion neuronal loss by adjunctive neurotrophin-3 in experimental pneumococcal meningitis

Abstract: BackgroundHearing loss is a frequent long-term complication of pneumococcal meningitis (PM). Its main pathological correlate is damage to the organ of Corti and loss of spiral ganglion neurons. The only current treatment option is cochlear implants which require surviving neurons. Here, we investigated the impact of systemically applied neurotrophin-3 (NT-3) on long-term hearing loss and the survival of neurons.MethodsEighteen hours after infection with S. pneumoniae, C57BL/6 mice were treated with a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…This is very similar to the mortality seen in humans in central Europe (2,3). Furthermore, we previously found that adjunctive dexamethasone significantly decreased hearing loss and its morphological correlates in the model of pneumococcal meningitis that was used here (34). Likewise, such a positive otoprotective effect of dexamethasone has been shown in adult patients with pneumococcal meningitis (39).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This is very similar to the mortality seen in humans in central Europe (2,3). Furthermore, we previously found that adjunctive dexamethasone significantly decreased hearing loss and its morphological correlates in the model of pneumococcal meningitis that was used here (34). Likewise, such a positive otoprotective effect of dexamethasone has been shown in adult patients with pneumococcal meningitis (39).…”
Section: Discussionsupporting
confidence: 56%
“…Dexamethasone, which was shown to be effective in human patients in central Europe (3,44), was of benefit not only in mice but also in meningitis models using adult rats, rabbits, and gerbils (34,(45)(46)(47). Nevertheless, even though dexamethasone seems of relatively strong benefit in these studies, its positive effect seems limited to patients treated in developed countries (39).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, the capability of ceftriaxone to reduce inflammation and apoptosis has been recently demonstrated. 30 Considering the Leung groups's experimental findings in an animal model of PD 6 and our data on the molecular interaction between ceftriaxone and α-synuclein, we thought to study the in vitro effects of ceftriaxone on viability and α-synuclein expression of PC12 cells exposed to 6-OHDA. Indeed, it is known that the treatment of neural cells with 6-OHDA reduces cell viability, 31 induces apoptosis, 32−34 and increases α-synuclein immunoreactivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%